Atheism and discrimination in the face of contemporary changes in the world - Łopuszańska, Urszula; Zacharska, Adrianna; Gierszon, Patrycja; Samardakiewicz, Marzena (Kultura-Społeczeństwo-Edukacja, 2020)
The aim of this article is to present the situation of atheists around the world in the face of political and cultural changes in the world due to the increase in religious radicalism, particularly Islamic one, migration and terrorism. The article is of an illustrative character and presents the review of English literature in the scope of the discussed subject matter. Furthermore, the results of the latest global reports on prevalence of atheism in the world and the phenomenon of discrimination against persons not identifying with any faith: atheists, humanists or freethinkers were presented. The results of the selected, recent studies on the social perception of atheists and the phenomena of discrimination against them were shown. Another raised issue was the new social movement called New Atheism widespread mainly in the countries of the Western culture that in the future can constitute a new social and political challenge. Conclusions: Between 2005 and 2012 the number of atheists increased by 3% and currently they constitute 13% of the population of the world, while the percentage of religious people decreased by 9%. Atheists like other minority groups are discriminated against and their situation is dependent on the country in which they live. However, the vast majority of countries in the world violates the rights of persons identifying themselves as atheists. Still, in some countries, the declaration of atheism is forbidden, and in 13 countries the death penalty can be imposed.